2005
DOI: 10.1002/neu.20137
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 activity of β‐bungarotoxin is essential for induction of cytotoxicity on cerebellar granule neurons

Abstract: The aim of this study was to investigate the mechanism of the cytotoxic effect of beta-bungarotoxin (beta-BuTX), a presynaptic neurotoxin, on rat cerebellar granule neurons (CGNs). The maturation of CGNs is characterized by the prominent dense neurite networks that became fragmented after treatment with beta-BuTX, and this cytotoxic effect of beta-BuTX on CGNs was in a dose- and time-dependant manner. The cytotoxic effect of beta-BuTX was found to be more potent than other toxins, such as alpha-BuTX, cardiotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Many phospholipase-like toxins are considered among the most potent toxins. Studies have reported that betabungarotoxin can induce more potent cytotoxic effects than other toxins such as alpha-bungarotoxin, cardiotoxin and melittin (Chen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many phospholipase-like toxins are considered among the most potent toxins. Studies have reported that betabungarotoxin can induce more potent cytotoxic effects than other toxins such as alpha-bungarotoxin, cardiotoxin and melittin (Chen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, β-BuTX effects would lead to an increase of excitability of cerebellar neurons. In general, the increase in excitability would correspond to a toxic action of β-BuTX by inducing neurotoxicity which is based on over-excitation of the neurons involving NMDA receptors [14,16,20,22,27,32]. In addition to that, by its phospolipase activity β-BuTX leads to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, by its phospolipase activity β-BuTX leads to apoptosis. Here, as a second effect, the products of phospholipase activity directly promote the signaling cascade leading to apoptosis [14-16,19,22,32]. Then the modulation of Na + channels to a higher activity would be a synergistic effect enhancing neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations